An Analysis of a Bike-Sharing System from a Business Model Perspective - Moro, Suzana Regina (2022)
Goal: Product-service systems are innovative business models that aim to contribute to sustainability issues. Bike-sharing system is a classic example of this kind of business model. This work covers an analysis of a bike-sharing system implemented in the South of Brazil from a business model perspective by focusing on the value network. Design/Methodology/Approach: Data was collected based on interviews with the executives of a focal company and information retrieved from other sources, e.g., company internal reports, PSS design documents, etc.). A research protocol was developed based on the literature to identify a set of variables to be interpreted. A semi-structured questionnaire was developed for interviews, which was recorded for later content transcription and analysis. Results: The business model value network and mechanisms of value proposition, configuration, delivery, and value capture are described. This business model is based on a diverse value network and should be developed and updated on co-creation mechanisms to deliver more sustainable results. Limitation of the investigation: It is a single study conducted in a medium-sized town in the South of Brazil that implemented a bike-sharing system. In addition, the analyis was considered in the “problem identification phase”. Practical implications: The bike-sharing business model analysis may improve the business model towards increasing the inhabitants' quality of life as well as city image. Originality/Value: The study was conducted in a developing country, analyzing a PSS business model from a sustainable operations perspective, which is not common in the current literature.